Kaidah-Kaidah Bahasa Arab Non-Fungsional: Upaya ‎Menghadirkan Materi Kaidah Bahasa Arab yang Lebih Mudah - Nurhaqiqi Nurhaqiqi (LISANIA: Journal of Arabic Education and Literature, 2019)
This study aims to further analyze some Arabic language rules that do not have semantic functions in a sentence; both rules derive from the nahwu and sharaf. The primary source of the study is the Arabic language rules analyzed using the text content (madhmûn) approach. The steps are firstly making an inventory of the rules stated anomaly, then finding its ‘illah (reason/cause), and then the conclusions are taken. The results of the study prove that there are Arabic rules that do not have semantic functions. This happens because the motive for its creation is not intended to present new intentions and meanings in a sentence. Among these motives are reasons for sentence efficiency, philosophical nuances and reasons for being mild in pronunciation. The patterns used are al-hadzf, al-ibdl, al-rutbah/taqdîm ta’khîr and al-ziyâdah. The results of this study are not in line with the 'traditional scholars such as al-Mâzinî, (d. 248 H), al-Mubarrid (d. 285 H.), al-Farrâ' (d. 189 H) who said that Arabic linguistics has been perfect and final and there is no need to review on it. On the contrary, this research strengthens the opinion of modern linguists such as Ibn Madlâ (d. 592 H), Syauqî Dhayf (born 1910 AD), Tammam Hasan (born 1918 AD) who said that Arabic science is convoluted, very philosophical and not apparently consistent, which must be reviewed to make it look lighter and easier to learn especially for beginners and finally the impression that Arabic is complicated, difficult and convoluted can be avoided.